Energy Storage Likely to Increase in Utility Resource Planning. Issue 10 (May 2016) - Higgins, Mark; Burgess, Ed; Ehrlich, Bill
Abstract : Today energy storage is a diverse asset class, and technological advances and rapid cost declines have now resulted in a wide array of energy storage technologies increasingly being deployed on utility systems across the country. Utilities from Hawaii to New York have been finding energy storage an extremely attractive and cost‐effective way to solve grid needs.